Successful Treatment of Testicular Failure Type IV Without Micro-Testicular Epididymal Sperm Extraction: A Case Report - Nahathai Paktinun; Chartchai Srisombut; Thidarat Kongwattanasin; Krit Pongpirul (Journal of Family and Reproductive Health, 2021)
Objective: Sperm donation and hormonal therapy with micro-Testicular Epididymal Sperm Extraction (TESE) for infertility from testicular failure might not always be available in some contexts. We report a successful embryo transfer from the patient-by ‘cumulative sperm collection’ strategy. Case report: A 42 year-old male presented with non-obstructive azoospermia from testicular failure. Hormonal treatments were given along with the patient-initiated ‘cumulative sperm collection’ strategy, which eventually resulted in 17 sperms retrieved. Twelve mature oocytes were selected for intracytoplasmic sperm injection (ICSI) with the retrieved sperms, of which 8 oocytes were successfully fertilized but only two reached the early blastocyst stage; the first embryo transfer was not successful. Another five eggs were thawed and fertilized with the remaining 5 sperms and 3 oocytes were successfully fertilized: Seven cells were grade 3, 6 cells were grade 3, and 3 cells were grade 3. The second embryo transfer was successful, and the term female infant was successfully delivered by cesarean section. Conclusion: At a center without micro-TESE availability, successful embryo transfer for testicular failure type IV could be achieved by hormonal therapy plus a ‘cumulative sperm collection’ strategy.